VD_FINDINFO HC / 2015 / 579 vom 23. Juni 2015 - VD Tribunal cantonal (2015)
LÉGITIMATION ACTIVE ET PASSIVE, VICE DE FORME, BAILLEURBAIL À LOYER | 29 al. 1 Cst., 132 al. 1 CPC (CH), 132 CPC (CH), 247 al. 2 CPC (CH), 2 al. 1 LJB